2005
DOI: 10.1258/004947505774938620
|View full text |Cite
|
Sign up to set email alerts
|

Drug use among adolescents in Ilorin, Nigeria

Abstract: The types and frequency of drug use among 1200 students aged 10-19 years was investigated and a prevalence rate of 40.1% found; currently used drugs included mild stimulants such as kolanut and coffee 294 (26.2%), alcohol 164 (14.5%), sniffing agents 80 (7.2%), amphetamine and ephedrine 66 (6.7%), cigarette 54 (4.8%), heroin 45 (4%) cocaine 40 (3.6%) and cannabis 38 (3.4%). Multiple drug use was found among the students, with the abuse of cannabis, cocaine and heroin being significant among those who smoked ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…This prevalence is higher than 14.5% obtained by Abdulkarim et al in Ilorin [17]. This high prevalence could be due to the fact that alcohol is widely available in Nigeria and easily accessible to various age groups.…”
Section: Discussionmentioning
confidence: 59%
“…This prevalence is higher than 14.5% obtained by Abdulkarim et al in Ilorin [17]. This high prevalence could be due to the fact that alcohol is widely available in Nigeria and easily accessible to various age groups.…”
Section: Discussionmentioning
confidence: 59%
“…Eneh and Stanley [2] found that 26% of secondary school students in Port Harcourt, Nigeria, used cannabis. Meanwhile, Abdulkarim et al [3] reported that 3.4% of students in Ilorin, Nigeria, currently used cannabis. In Zimbabwe, Khan and Arnott [4] found that 3.4% of students in rural secondary schools had ever used cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…[1] It is second only to dental caries as a cause of tooth loss among adults in developed countries. [2]…”
Section: Introductionmentioning
confidence: 99%